Promising ethanol detection enhancement of Cu2O thin film deposited by GLAD technique. (February 2020) - Ben Nacer, S.; Jlidi, D.; Labidi, A.; Chaffar Akkari, F.; Touihri, S.; Maaref, M.
Highlights: Sensing properties of GLAD Cu2 O were influenced by the deposition angle. Ethanol sensitivity was improved due to increases of porosity with the increases of deposition angle. GLAD Cu2 O layers exhibit good sensitivity towards ethanol in the ppm range. Only surfacic adsorbed oxygen contributes to the Cu2 O layers responses. Abstract: The purpose of this proposed work is the study of optical, morphological, structural and electrical properties of copper oxide (Cu2 O) thins layers deposed by the technique of Glancing angle deposition (GLAD) for ethanol sensor application, for that the thickness variation effect of the layer on the various properties and its link with the deposition time of the layer on the glass substrate. It was found that the increases of deposition angle increase the layer sensitivity to ethanol as a result of the increases of porosity, decreases of layer thickness and increases of granular surface morphology.